Economic impacts of climate change on priority value chains in the Caribbean: Implications for private-sector investment and scaling-up of climate-smart agriculture in the region - Rhiney, Kevon; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2018)
To support the implementation of CTA’s flagship project for the Caribbean, this report is aimed at developing capacity-building efforts for specific groups of farmers engaging in specific production activities in priority value chains so they may improve their access to key markets. This report focuses on the threats climate change poses to the production of two priority value chains in the Caribbean – fruit and vegetables, and roots and tubers.